2012
DOI: 10.1073/pnas.1212826109
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic peptoid oligomers as dual-action antifreeze agents

Abstract: The ability of natural peptides and proteins to influence the formation of inorganic crystalline materials has prompted the design of synthetic compounds for the regulation of crystal growth, including the freezing of water and growth of ice crystals. Despite their versatility and ease of structural modification, peptidomimetic oligomers have not yet been explored extensively as crystallization modulators. This report describes a library of synthetic N-substituted glycine peptoid oligomers that possess "dual-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 51 publications
0
66
0
Order By: Relevance
“…There are numerous examples of crystallization systems that are perturbed by linear impurities, leading to strong nonlinear step kinetics. Notable examples are peptide-biomineral systems (calcite [22], apatite [23], calcium oxalate monohydrate [24,25]) and anti-freeze polymer, and ice [26,27]. In fact, stop-and-go dynamics were also observed by Weaver et al for calcium oxalate monohydrate [25].…”
mentioning
confidence: 77%
“…There are numerous examples of crystallization systems that are perturbed by linear impurities, leading to strong nonlinear step kinetics. Notable examples are peptide-biomineral systems (calcite [22], apatite [23], calcium oxalate monohydrate [24,25]) and anti-freeze polymer, and ice [26,27]. In fact, stop-and-go dynamics were also observed by Weaver et al for calcium oxalate monohydrate [25].…”
mentioning
confidence: 77%
“…Several commercially successful and clinically significant taxoids have been developed, such as paclitaxel (PTX), docetaxel (DTX), and cabazitaxel (CBZ)[1]. They are heavily used in the treatment of breast, lung and ovarian cancer as well as other malignancies [2,3]. Unfortunately, these taxoids suffer from two major setbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Peptoid oligomers that bind to ice and mimic antifreeze proteins may also guide the design of new hosts. 112 Perhaps the ultimate challenge in protein recognition -the recognition of individual residues on an open surface -is difficult, but pioneering work has shown that rare residues such as those post-translationally modified in histone proteins can be successfully targeted. 113 What about enzyme mimicry?…”
Section: Recognition Mimicry and Interactions With Biomoleculesmentioning
confidence: 99%